2014
DOI: 10.1111/anu.12066
|View full text |Cite
|
Sign up to set email alerts
|

Partial replacement of fish meal by several plant proteins with or without iron and lysine supplement in diets for juvenile Chinese sucker,Myxocyprinus asiaticus

Abstract: Two feeding experiments were conducted to evaluate the potential of fermented soybean meal (FSBM), corn gluten meal (CGM) and cottonseed meal (CSM) with or without lysine (L) and iron (Fe) to replace fish meal (FM) in practical diets of juvenile Chinese sucker. In experiment I, four experimental diets (430 g kg−1 crude protein on dry matter basis) were formulated. Diet containing FM as the main protein source was used as a control (Diet 1). Diets 2–4 had 300 g kg−1 FM protein replaced with FSBM, CGM or CSM pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…However, either ML or CL supplementation was quite effective in improving the nutritive values of the RPC diet as fish fed both diets achieved similar results with FM group. Similar results were also observed in red sea bream ( pagrus major ) (Kader, Koshio, Ishikawa, Yokoyama, & Bulbul, ) and Chinese sucker ( Myxocyprinus asiaticus ) (Yu, Gong, Lin, & Yuan, ). In contrast, other studies indicated that dietary CAAs could not be efficiently used by some aquatic species compared to protein‐bound AAs (Hauler et al., ; Peres & Oliva‐Teles, ).…”
Section: Discussionsupporting
confidence: 79%
“…However, either ML or CL supplementation was quite effective in improving the nutritive values of the RPC diet as fish fed both diets achieved similar results with FM group. Similar results were also observed in red sea bream ( pagrus major ) (Kader, Koshio, Ishikawa, Yokoyama, & Bulbul, ) and Chinese sucker ( Myxocyprinus asiaticus ) (Yu, Gong, Lin, & Yuan, ). In contrast, other studies indicated that dietary CAAs could not be efficiently used by some aquatic species compared to protein‐bound AAs (Hauler et al., ; Peres & Oliva‐Teles, ).…”
Section: Discussionsupporting
confidence: 79%
“…This result is similar to past research revealed that replacing fish meal by a mixture of different plant protein sources showed better growth performance in Nile Tilapia (Oreochromis niloticus L.) (Al-Thobaiti et al, 2018). Some studies also revealed that the used of soybean meal (Mo et al, 2016), cotton seed meal (Yu et al, 2014), seaweed (Gracillaria arcuate) (Al-Asgah et al, 2016) have significant effects on the growth of fish. The FCR and FE both are related to dietary protein intake and can be converted into fish weight gain (Koumi et al, 2009).…”
Section: Resultssupporting
confidence: 90%
“…The activity of intestinal digestive enzymes is an important indicator reflecting the ability of feed digestion [46]. In parallel with the aforementioned findings in ADC values, dietary FSBM also remarkably ameliorated SBM-induced decrease of the intestinal digestive enzymes (trypsin, lipase and diastase) activities.…”
Section: Discussionmentioning
confidence: 62%